2011
DOI: 10.1037/a0021400
|View full text |Cite
|
Sign up to set email alerts
|

The PANAS structure revisited: On the validity of a bifactor model in community and forensic samples.

Abstract: The Positive and Negative Affect Schedule (PANAS) is a widely used inventory for the assessment of affect in psychology and other applied sciences. Despite its popularity, the structure of the PANAS is still under debate. On the one hand, there is evidence of the traditional 2-factor model with Positive Affect (PA) and Negative Affect (NA) as uncorrelated factors. On the other hand, a more complex structure of the PANAS has been discussed. To shed further light on the core dimensions of the PANAS, 2 studies in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
125
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(139 citation statements)
references
References 84 publications
(126 reference statements)
11
125
1
2
Order By: Relevance
“…Data from the validation sample suggested that people generally endorse greater levels of PA ( M = 35.0, SD = 7.9), compared to NA ( M = 18.1, SD = 5.9), such that the distributions display negative (PA) and positive (NA) skew (Watson et al, 1988). These findings, which help approximate the relative frequency of a given PANAS score, have been reproduced in community and clinical samples (e.g., Crawford and Henry, 2004; Leue and Beauducel, 2011; Watson and Clark, 1994). PANAS scores have demonstrated adequate internal consistency reliability, test-retest reliability, and convergent and discriminant validity (Watson et al, 1988; Watson and Clark, 1994); however, the factor structure has been more widely disputed.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Data from the validation sample suggested that people generally endorse greater levels of PA ( M = 35.0, SD = 7.9), compared to NA ( M = 18.1, SD = 5.9), such that the distributions display negative (PA) and positive (NA) skew (Watson et al, 1988). These findings, which help approximate the relative frequency of a given PANAS score, have been reproduced in community and clinical samples (e.g., Crawford and Henry, 2004; Leue and Beauducel, 2011; Watson and Clark, 1994). PANAS scores have demonstrated adequate internal consistency reliability, test-retest reliability, and convergent and discriminant validity (Watson et al, 1988; Watson and Clark, 1994); however, the factor structure has been more widely disputed.…”
Section: Introductionmentioning
confidence: 77%
“…For example, Crawford and Henry (2004) found that the bivariate model with a PA-NA intercorrelation and correlated uniquenesses fit better than Mehrabian's hierarchical model (notably, correlated uniquenesses were not included in any of the three-factor models in this study). Additionally, Leue and Beauducel (2011) produced a different model in which a general first-order factor termed Affective Polarity was added to the bivariate model. It has also been suggested that both the oblique two- and three-factor structures are plausible, but that the three-factor model provides superior fit (Killgore, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, there is an ongoing discussion regarding the dimensionality of affect (e.g., Leue & Beauducel, 2011; Schimmack & Grob, 2000), with cross-Atlantic differences between North America (favoring 2-dimensional models) and Europe (favoring 3-dimensional models). Although 3-dimensional models appear to out-perform 2-dimensional models with regard to data fit (Leue & Beauducel, 2011; Schimmack & Grob, 2000), even 3-dimensional models are not sufficient to distinguish between specific basic emotions (Schimmack & Grob, 2000). Furthermore, opinions differ as to whether trait measures can be used to assess state affect because they are thought to differ in their structure, which may preclude their mutual use (Schimmack & Grob, 2000; Schimmack et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…(e) Finally, and regarding the shape effect, findings on the underlying structure of affect may be biased if variations on trait measures also reflect state variation. For example, the PANAS has often been applied across age groups, normal and clinical populations, and countries to ascertain its construct validity (Leue & Beauducel, 2011). If the measures confound state and trait, insights about affect structure are not clearly attributable to state or trait, but represent a mixture of both.…”
Section: Implications Of Findingsmentioning
confidence: 99%